Ecology, Folklore, and Land: Kumpulan Cerita Rakyat Papua as Preventive Education - Sugeng Santoso; Nazla Maharani Umaya; Setia Naka Andrian (Idarah (Jurnal Pendidikan dan Kependidikan), 2025)
Papua faces significant environmental problems and agrarian conflicts due to the exploitation of natural resources. This condition underscores the urgent need for environmental education rooted in local wisdom to foster sustainable practices. This research aims to identify ecological elements within Kumpulan Cerita Rakyat Papua, a folklore collection published by Balai Bahasa Papua in 2017, and examine their relevance to environmental education policies in schools. Employing a qualitative descriptive method, this paper utilizes Greg Garrard’s ecocriticism framework to analyse these elements. Purposive stratified sampling was used to select representative samples from 19 stories, followed by thematic analysis to uncover key themes. Data validity was ensured through the principles of trustworthiness including credibility, dependability, confirmability, and transferability. The findings reveal prominent ecological elements such as wilderness, animals, dwelling, the earth, pollution, apocalypse, and pastoral motifs, illustrating a harmonious humans-nature relationship in Papuan culture. Papuan folklore serves as a vital medium for transmitting ecological knowledge, which can be seamlessly integrated into school curricula, particularly in Indonesian Language subjects. By integrating ecological values into education, this research advocates for building environmental awareness from an early age, empowering younger generations to contribute to nature preservation and effectively addressing agrarian conflicts in Papua, reducing resource-driven tensions through informed, community-based learning.